Functionalized Allenes: Generation by Sigmatropic Rearrangement and Application in Heterocyclic Chemistry - Banert, Klaus (Current Organic Chemistry, 2019)
The present review article summarizes the synthesis of allenes, which bear an adjacent functional group, by [3,3]- or [2,3]-sigmatropic rearrangement of appropriate propargyl substrates. Functionalized allenes, such as allenyl isothiocyanates, isoelenocyanates, isocyanates, thiocyanates, azides, azo compounds and others, are easily available by these methods. In several cases, however, the title compounds show high reactivity, which leads to rapid intermolecular or intramolecular successive reactions. Consequently, synthesis of the allenes by sigmatropic rearrangement has to be combined with special techniques, for example, flash vacuum pyrolysis or in situ generation and trapping reactions. The high tendency of the presented functionalized allenes to undergo cyclization reactions can be utilized to prepare heterocyclic products, for instance, thiazoles, selenazoles, 1,2,3-triazoles and pyrazoles. The synthesis of functionalized 1,3-butadienes by a second sigmatropic rearrangement of the title compounds is also successful.
Keywords: Allenes